The Trend of Multimodal Use in School Learning from The Past to The Future : A Systematic Literature Review - Ekowati, Dyah Worowirastri; Husamah, Husamah; Setyaningrum, Rina Wahyu; Sumarsono, Puji (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to investigate the trends of multimodal use in school learning from the past to the future as an important reflection for education practitioners. This research used SLR method with 19 articles that met the criteria for analysis after inclusion and exclusion process used PRISMA. The result showed that a total of 19 articles conducted research using the most dominant approach, namely a qualitative approach of 73.68% followed by a mixed and quantitative approach. The main keywords that often appear using the VOSviewer application are multimodality, learning, school, and literacy. Related keywords that do not have a direct relationship with multimodality are digital media, media literacy, school, creativity, and cyberspace. This is an opportunity for future research. Regarding the country of origin of the authors, the most are from Australia, namely five articles. The results of the analysis using VOSviewer on the 19 articles showed that Neil Mercer had the most publications cited by other articles. The analysis of the 19 articles illustrates that the most frequent contribution is the development of learning materials, both virtual and non-virtual, using various media, ranging from manual to smartphones. The results of this study provide valuable insights and implications for current and future education policies, particularly in guiding the integration of multimodal learning approaches in schools. These findings offer a foundation for researchers and policymakers to explore and develop strategies aligned with diverse educational objectives and backgrounds..